A non-affinity purification process for GMP production of prefusion-closed HIV-1 envelope trimers from clades A and C for clinical evaluation. Issue 25 (8th June 2021) - Gulla, Krishana; Cibelli, Nicole; Cooper, Jonathan W.; Fuller, Haley C.; Schneiderman, Zachary; Witter, Sara; Zhang, Yaqiu; Changela, Anita; Geng, Hui; Hatcher, Christian; Narpala, Sandeep; Tsybovsky, Yaroslav; et al.
Highlights: Purification of clade A and C HIV-1 envelope (Env) trimers by a novel non-affinity method. Env trimers produced in pre-fusion closed conformation without antibody capture. Non-affinity purified trimers show minimal exposure of CD4-induced or V3 epitopes. Scalable process yields up to 0.2 g/L of purified prefusion-closed HIV-1-Env trimer. Abstract: Metastable glycosylated immunogens present challenges for GMP manufacturing. The HIV-1 envelope (Env) glycoprotein trimer is covered by N -linked glycan comprising half its mass and requires both trimer assembly and subunit cleavage to fold into a prefusion-closed conformation. This conformation, the vaccine-desired antigenic state, is both metastable to structural rearrangement and labile to subunit dissociation. Prior reported GMP manufacturing for a soluble trimer stabilized in a near-native state by disulfide (SOS) and Ile-to-Pro (IP) mutations has employed affinity methods based on antibody 2G12, which recognizes only 30% of circulating HIV strains. Here, we develop a scalable manufacturing process based on commercially available, non-affinity resins, and we apply the process to current GMP (cGMP) production of trimers from clades A and C, which have been found to boost cross-clade neutralizing responses in vaccine-test species. The clade A trimer, which we named "BG505 DS-SOSIP.664", contained an engineered disulfide (201C-433C; DS) within gp120, which further stabilized this trimer in a prefusion-closed conformation resistant to CD4-induced triggering. BG505 DS-SOSIP.664 was expressed in a CHO-DG44 stable cell line and purified with initial and final tangential flow filtration steps, three commercially available resin-based chromatography steps, and two orthogonal viral clearance steps. The non-affinity purification enabled efficient scale-up, with a 250 L-scale cGMP run yielding 9.6 g of purified BG505 DS-SOSIP.664. Antigenic analysis indicated retention of a prefusion-closed conformation, including recognition by apex-directed and fusion peptide-directed antibodies. The developed manufacturing process was suitable for 50 L-scale production of a second prefusion-stabilized Env trimer vaccine candidate, ConC-FP8v2 RnS-3mut-2G-SOSIP.664, yielding 7.8 g of this consensus clade C trimer. The successful process development and purification scale-up of HIV-1 Env trimers from different clades by using commercially available materials provide experimental demonstration for cGMP manufacturing of trimeric HIV-Env vaccine immunogens, in an antigenically desired conformation, without the use of costly affinity resins.